2018
DOI: 10.1002/ijgo.12704
|View full text |Cite
|
Sign up to set email alerts
|

Clinical guidelines—the challenges and opportunities: What we have learned from the case of misoprostol for postpartum hemorrhage

Abstract: Objective To establish whether national guidelines for postpartum hemorrhage (PPH) reflect new scientific evidence on misoprostol, and determine the challenges faced in their implementation. Methods A web‐based survey was sent by email to 130 national societies of obstetrics and gynecology (FIGO Member Associations) in 2016. The survey, composed of 18 questions, covered national guidelines on PPH with particular reference to misoprostol, the creation of national guidelines, and challenges to implementation. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A key component of this management is the use of a uterotonic medication, such as oxytocin, which is administered either intramuscularly or intravenously immediately following the birth of the baby. In settings where oxytocin is unavailable, misoprostol can be used, which has the advantage of being heat-stable and can be administered orally, rectally or sublingually (Morris and Khatun, 2019;WHO, 2018). Oxytocin and misoprostol are life-saving uterotonic medications for the treatment of PPH in cases of uterine atony.…”
Section: Introductionmentioning
confidence: 99%
“…A key component of this management is the use of a uterotonic medication, such as oxytocin, which is administered either intramuscularly or intravenously immediately following the birth of the baby. In settings where oxytocin is unavailable, misoprostol can be used, which has the advantage of being heat-stable and can be administered orally, rectally or sublingually (Morris and Khatun, 2019;WHO, 2018). Oxytocin and misoprostol are life-saving uterotonic medications for the treatment of PPH in cases of uterine atony.…”
Section: Introductionmentioning
confidence: 99%
“…9,15 Although significant improvement was achieved in the prevention and management of PPH as a main obstetric near-miss, maternal mortality rates remain high in Kazakhstan. 10,23,24 To our knowledge, this is the first study to identify the prevalence, indications, and outcomes of peripartum hysterectomy in Kazakhstan using nationwide large-scale health-care data for the period of 5 years (2014-2018).…”
Section: Discussionmentioning
confidence: 99%
“…The adverse effects of misoprostol, such as nausea, vomiting, diarrhoea, fever, and chills, are dosedependent. The recommended dose of misoprostol for prevention of PPH is 600 mg. 11 Previous studies in Benin, Nigeria, and Egypt showed that that the mean intraoperative blood loss volume was significantly lower in the sublingual than rectal group. [12][13][14][15] However, sublingual misoprostol use had more maternal side effects than rectal use.…”
Section: Introductionmentioning
confidence: 99%